INFLUENCE AT WORK, ORGANIZATIONAL COMMITMENT, AND PERFORMANCE OF WORK MOTIVATION OF EMPLOYEES (STUDY ON CITY taps TIRTA MOEDAL Semarang) - Dwi Putri Suryani, 10.05.51.0020; Yunianto, Askar (Students Journal of Economic and Management, 2014)
This study aims to identify and analyze the influence of the work environment, organizational commitment, and work motivation on employee performance PDAM Tirta Moedal Semarang. Its population is employees PDAM Tirta Moedal Semarang totaling 131 employees. Given the population, then it deserves to be sampled. The sampling technique used is Loading Factor. The analytical tool used in this study is the Multiple Linear Regression Analysis, which previously conducted test validity and reliability, to test the effect of partially magnitude of each variable as follows Y = 0,365X1 + 0,261X2 + 0,193X3. And the results of the coefficient of determination calculation of Adjusted R Square is equal to 0.521, or by 52.1%, which means a change in the dependent variable (Y) can be explained by the influence of the work environment variables (X1), organizational commitment (X2), and motivation (X3) , while the rest is influenced by other variables not tested or described in this research. The results of hypothesis testing showed a positive and significant relationship between the work environment, organizational commitment, and work motivation on employee performance. Keywords: Work Environment, Organizational Commitment, Job Motivation, Employee Performance